Mycobacterium haemophilum scleritis: two case reports and review of literature - Punyanuch Pisitpayat (2020)
BACKGROUND: Mycobacterium haemophilum is a rare and emerging nontuberculous mycobacteria (NTM). It normally causes localized or disseminated systemic diseases, particularly skin infections and arthritis in severely immunocompromised patients. There have been 5 cases of M. haemophilum ocular infections reported in the literature. Only 1 case presented with scleritis with keratitis. Here, we reported 2 cases of M. haemophilum scleritis. One of them was immunocompetent host and had keratitis with radial keratoneuritis as a presenting sign. CASE PRESENTATION: Case 1: A 52-year-old Thai female with rheumatoid arthritis presented with scleritis. Conjunctival scraping was carried out and the culture result was positive for M. haemophilum. Despite receiving systemic and topical antibiotics, her clinical symptoms and signs worsened. Surgical debridement was performed. After surgery, the lesion was significantly improved and finally turned to conjunctival scarring. Case 2: A 32-year old healthy Thai male without underlying disease presented with nodular scleritis and keratouveitis with multiple radial keratoneuritis. Surgical debridement of the scleral nodule was performed. Initial microbiological investigations were negative. Herpes ocular infections was suspected. Topical antibiotics, oral acyclovir, low-dose topical steroids and systemic steroids were started. The scleral inflammation subsided but later the keratitis relapsed, requiring corneal biopsy. Histopathology of the specimen revealed acid-fast bacteria and M. haemophilum was identified by polymerase chain reaction (PCR) and sequencing. The diagnosis of Mycobacterial keratitis was made. Although using the combination of systemic and topical antibiotics, his clinical status progressively deteriorated. Multiple therapeutic penetrating keratoplasties were required to eradicate the infection. No recurrence was found during the 1-year follow-up in both cases. CONCLUSIONS: M. haemophilum can cause scleritis and keratitis, even in immunocompenent host. Radial keraoneuritis is first described in M. haemophilum keratitis. NTM keratitis should be considered in the differential diagnosis of patients with radial keratoneuritis. Increased awareness and early diagnosis using appropriate culture conditions and molecular techniques are important for the proper treatment of this infection. Prompt surgical intervention appears to be vital for successful management of M. haemophilum scleritis and keratitis.